Individual and environmental factors underlying life space of older people - study protocol and design of a cohort study on life-space mobility in old age (LISPE) - Rantanen Taina; Portegijs Erja; Viljanen Anne; Eronen Johanna; Saajanaho Milla; Tsai Li-Tang; Kauppinen Markku; Palonen Eeva-Maija; Sipilä Sarianna; Iwarsson Susanne; Rantakokko Merja (BMC, 2012)
Abstract Background A crucial issue for the sustainability of societies is how to maintain health and functioning in older people. With increasing age, losses in vision, hearing, balance, mobility and cognitive capacity render older people particularly exposed to environmental barriers. A central building block of human functioning is walking. Walking difficulties may start to develop in midlife and become increasingly prevalent with age. Life-space mobility reflects actual mobility performance by taking into account the balance between older adults internal physiologic capacity and the external challenges they encounter in daily life. The aim of the Life-Space Mobility in Old Age (LISPE) project is to examine how home and neighborhood characteristics influence people's health, functioning, disability, quality of life and life-space mobility in the context of aging. In addition, examine whether a person's health and function influence life-space mobility. Design This paper describes the study protocol of the LISPE project, which is a 2-year prospective cohort study of community-dwelling older people aged 75 to 90 (n = 848). The data consists of a baseline survey including face-to-face interviews, objective observation of the home environment and a physical performance test in the participant's home. All the baseline participants will be interviewed over the phone one and two years after baseline to collect data on life-space mobility, disability and participation restriction. Additional home interviews and environmental evaluations will be conducted for those who relocate during the study period. Data on mortality and health service use will be collected from national registers. In a substudy on walking activity and life space, 358 participants kept a 7-day diary and, in addition, 176 participants also wore an accelerometer. Discussion Our study, which includes extensive data collection with a large sample, provides a unique opportunity to study topics of importance for aging societies. A novel approach is employed which enables us to study the interactions of environmental features and individual characteristics underlying the life-space of older people. Potentially, the results of this study will contribute to improvements in strategies to postpone or prevent progression to disability and loss of independence.